Nanoparticles: heating tumors to death?. (January 2011) - Vauthier, Christine; Tsapis, Nicolas; Couvreur, Patrick
Thermotherapy consisting of heating tumors to death appears to be a suitable method to achieve tumor ablation in a noninvasive manner with minimal side effects but developments were hampered because of the lack of specificity of the heating method. New interests have emerged by introducing nanoparticles as energy absorbent agents in tumor tissue to locally enhance the action of irradiation, hence increasing the specificity of the method. Mechanisms of tumor death depend on the nature of the nanoparticles and irradiation modalities. They can be induced either by heat-dependant or by heat-independent phenomena. As discussed in this article, it can reasonably be expected that the recent methods of thermotherapy developed with nanoparticles have a tremendous potential for cancer treatments. However, overcoming challenging milestones is now required before the method will be ready for the treatment of a wide range of cancers.